ANTECEDENTS OF PURCHASING ECO-FRIENDLY SHOPPING BAGS: THE MEDIATION ROLE OF GREEN AWARENESS - Puspa Novita Sari; Lorena Dara Putri Karsono (Journal of Finance, Economics and Business, 2023)
The increasing amount of plastic waste that threatens the sustainability of ecosystems and has adverse effects on the environment and health needs to be addressedcollectively. One solution that can be offered is to replace the use of plastic bags with eco-friendly shopping bags. Eco-friendly shopping bags are made of recyclable environment materials, thus helping to reduce plastic waste that pollutes the environment. This study aims to identify the factors that influence the purchasing decision of eco-friendly shopping bags, considering green awareness factors through causal and mediation testing. The data analysis method used in this study is the Structured Equation Model (SEM) using the Smart PLS application. Sampling was carried out using purposive sampling method, and 153 research samples were obtained. Respondents in this study were consumers who have purchased shopping bag products at Alfamart stores throughout the Solo Raya region. The results show that green rerceived value and green brand image have a positive and significant effect on purchase decision through green awareness as an intervening variable. This study implies that Alfamart needs to initiate a strategy to increase green perceived value and green brand image through green awareness so that it can influence the purchasing decision of eco-friendly shopping bags. With the increase in the number of eco-friendly shopping bag users, it is expected to reduce the use of plastic bags that can have a detrimental impact on the environment.